Electrochemical NADH regeneration and electroenzymatic CO2 reduction on Cu nanorods/glassy carbon electrode prepared by cyclic deposition. (20th August 2016) - Kim, Seung-Han; Chung, Gui-Yung; Kim, Seong-Hoon; Vinothkumar, G.; Yoon, Sung-Ho; Jung, Kwang-Deog
Graphical abstract: Abstract: Mimicking photosynthesis using NADH is a sustainable method to convert CO2 and mitigate global warming. Here, Cu nanorods with twin crystal structure on glassy carbon (GC) were prepared by a cyclic electrodeposition method with voltage from −0.2 V to −1.0. The prepared CuGC electrodes were used for the electrochemical NADH regeneration and electroenzymatic CO2 reduction at −1.0 V using formate dehydrogenase from Candida boidinii . The selective activation of NADH (1, 4-NADH) approached 67% as the deposition cycle number increased. The electron mediator [Cp*Rh(bpy)Cl]Cl complex (Rh(III)) was used to obtain nearly 100% active NADH on the CuGC electrode. The electron transfer rate to Rh(III) is crucial for optimal NADH regeneration: Rh(III) should be reduced to RhH quickly as it has the capability to decompose NADH catalytically. This allows sufficiently high NAD + conversion and NADH regeneration reaction rates for the electroenzymatic CO2 reduction to formate. The optimum concentrations of Rh(III) and NAD + were estimated to be 0.25 and 1.00 mM, respectively. For the CuGC electrode prepared with 300 deposition cycles, the formate formation rate was estimated to be (6.28 ± 0.02) × 10 −3  μmol/mg Cbs FDH /min, a three-fold increase compared to previously reported results on Cu foil electrode.